Radical reporting : writing better audit, risk, compliance, and information security reports - James, Sara I. (Security, audit and leadership series, 2022)
"Most people dread writing reports; they also dread reading reports. What they don't realize is that the techniques that make writing more readable make it more powerful. This is especially relevant for professionals in areas such as audit, risk, compliance, and information security. This small volume provides the tools and techniques needed to improve reports. It does so through addressing crucial concepts all too often overlooked in the familiar rush to perform tasks, complete projects, and meet deadlines. These concepts - the role of culture in communication; the link between logic and language; the importance of organizing thoughts before writing; and how to achieve clarity - may seem academic or theoretical. They're not. Unless writers understand their own thoughts, actions, and objectives, they cannot hope to communicate them at all - let alone clearly"--